Low-velocity impact behaviour of woven laminate plates with fire retardant resin - Grasso, Marzio; Xu, Yigeng; Ramji, Amit; Zhou, Gang; Chrysanthou, Andreas; Haritos, George; Chen, Yong Kang (Elsevier, 2019)
The understanding of the damage mechanisms for woven laminate plates under low-velocity impact is challenging as the damage mechanisms at the interface of adjacent layers are dominated by the fibre architecture. This work presents an experimental investigation of the behaviour of woven glass and carbon fibre composite laminates in a matrix of fire retardant resin under low-velocity impact. The performance is evaluated in terms of damage mechanisms and force time history curves. Six impact energy levels were used to test standard plates to identify the type of damage observed at various energy levels. Scanning electron microscopy (SEM) along with C-scans were used to characterise the damage. It has been observed that in woven composites, the damage occurs mostly between the fibre bundles and matrix. As the impact energy increases, the failure involves extended matrix cracking and fibre fracture. Moreover, due to the fibre architecture, both the contact forces between bundles of fibres and stretching of the bundles are responsible for the dominant matrix cracking damage mode observed at the low-impact energy level. As the impact energy increases, the damage also increases resulting in fibre fracture. The experimental evidence collected during this investigation shows that for both the carbon fibre and the glass fibre woven laminates the low-velocity impact behaviour is characterised by extended fibre fracture without a noticeable sudden load drop.
Keywords: Low-velocity impact; Woven composite; Delamination; Matrix crack; Fibre breakage